Ubiquitous Learning Grid: self-building knowledge in cross-boundary virtual learning communities. (6th September 2011) - Chang, Cheng-Sian; Chen, Tzung-Shi
Recent advances in Information and Communication Technologies, especially web technology, mean not only that e-learning is unlimited in location of computers, but also that learners can study in the virtual learning environment. This situation may present some problems, such as social skills, personalisation/individualisation, self-regulated learning skills and communication problem. To resolve these problems, this study provides a cyclic model of self-building knowledge conversion including learning community, learning resource and realistic world. This model provides a Ubiquitous Learning Grid service. With this service, learners will desire to become knowledgeable through sharing, exchanging, communicating and discussing with other members of the community.